Effects of electric and magnetic charges on weak deflection angle and bounding greybody of black holes in nonlinear electrodynamics - Javed, Wajiha; Atique, Mehak; Övgün, Ali (Elsevier, 2023)
In this paper, we study the weak deflection angle using the Gauss-Bonnet theorem and bounding greybody factor for electric and magnetic black holes in the background of nonlinear electrodynamics. Using Gibbons and Werner's approach, we first acquired the Gaussian optical curvature to be used in the Gauss-Bonnet theorem and calculate the bending angle for spherically symmetric electric and magnetic black holes in both non-plasma and plasma mediums in the weak field limits. Later, we calculate the rigorous bounds of the greybody factor for the given black holes. Furthermore, we are looking into the graphical behaviour of bending angles and greybody bounds at specific values of multiple parameters as well as black hole charges. It is to be mentioned here that all the results for the electric and magnetic-charged black hole solutions are reduced into the Schwarzschild black hole solution in the absence of the black hole charges.
Keywords: Gravitational lensing; Black holes; Gauss-bonnet theorem; Plasma medium; Greybody factor; Nonlinear electrodynamics